Suction/Injection Effect on a Boundary Layer Flow Past a Stretching Cylinder with Slip Condition - Muhammad Khairul Anuar, Mohamed; Hasmawani, Hashim; Nor Aida Zuraimi, Md Noar; Norhafizah, Md Sarif; Mohd Zuki, Salleh; Anuar, Ishak (Universiti Malaysia Pahang, 2016)
In this study, the mathematical modeling for boundary layer flow and heat transfer on a stretching cylinder with suction/blowing effect and velocity slip condition is considered. The transformed boundary layer equations are solved numerically using the Runge-Kutta-Fehlberg method. The numerical solutions are obtained for the reduced Nusselt number and skin friction coefficient as well as the velocity and the temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, Reynolds number, stretching parameter, suction/injection parameter and velocity slip parameter are analyzed and discussed.